SITE-UL BIBLIOTECII MUNICIPALE „B.P. HASDEU” – INSTRUMENT DE INFORMARE, INTERACŢIUNE, PROMOVARE ȘI COMUNICARE PROFESIONALĂ - GONŢA, șef serviciu, Departamentul tehnologia informaţiei, Maria (BIBLIOPOLIS, 2020)
The site of the Municipal Library "B.P. Hasdeu" is a tool for information, interaction, communication and professional promoting. It provides information on activity of network branches, information services and electronic resources provided by the library. The article describes the structure, the importance and the use of website and is an opportunity to know www. hasdeu.md.